2008
DOI: 10.1182/blood-2007-03-076679
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome following hematopoietic stem-cell transplantation in Wiskott-Aldrich syndrome: collaborative study of the European Society for Immunodeficiencies and European Group for Blood and Marrow Transplantation

Abstract: Wiskott-Aldrich syndrome (WAS) is a rare X-linked immunodeficiency with microthrombocytopenia, eczema, recurrent infections, autoimmune disorders, and malignancies that are life-threatening in the majority of patients. In this long-term, retrospective, multicenter study, we analyzed events that occurred in 96 WAS patients who received transplants between 1979 and 2001 who survived at least 2 years following hematopoietic stem-cell transplantation (HSCT). Events included chronic graft-versus-host disease (cGVHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
198
2
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 210 publications
(216 citation statements)
references
References 43 publications
(42 reference statements)
6
198
2
10
Order By: Relevance
“…For example, while most children with primary immunodeficiency disorders such as SCID develop normal immune function with a low level of donor chimerism, some children with Wiskott-Aldrich syndrome may require CDC to control symptoms of autoimmunity. 22,23 The incidence of increasing MC was 33% in our study which is within the range of published results. Hoelle et al 4 reported an incidence of 13% in a cohort of children with severe aplastic anemia receiving CD34 þ enriched transplants, and Willasch et al 11 reported a 34% incidence of increasing MC in children with non-malignancies conditioned with busulfan, cyclophosphamide and antithymocyte globulin, 70% of whom received T-cell depleted transplants.…”
Section: Discussionsupporting
confidence: 78%
“…For example, while most children with primary immunodeficiency disorders such as SCID develop normal immune function with a low level of donor chimerism, some children with Wiskott-Aldrich syndrome may require CDC to control symptoms of autoimmunity. 22,23 The incidence of increasing MC was 33% in our study which is within the range of published results. Hoelle et al 4 reported an incidence of 13% in a cohort of children with severe aplastic anemia receiving CD34 þ enriched transplants, and Willasch et al 11 reported a 34% incidence of increasing MC in children with non-malignancies conditioned with busulfan, cyclophosphamide and antithymocyte globulin, 70% of whom received T-cell depleted transplants.…”
Section: Discussionsupporting
confidence: 78%
“…Conversely, patients receiving cord blood stem cells in conjunction with serotherapy had a tendency to more mixed donor chimerism. Although donor myeloid chimerism was sufficiently high to cure most patients with CGD and WAS with all donor types/stem cell sources, where 100% donor chimerism might be preferred in all cell lineages (eg, WAS), 25 then the use of PBSCs or full myeloablation with busulfan might be required.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical symptoms are usually severe in those classic WAS patients with chronic eczema and frequent lymphadenopathy and hepatosplenomegaly (1). Moreover, patients with the classic WAS phenotype should be usually treated with allogeneic HSCT (7). It is vital to treat classic WAS patients with severe symptoms and infections as soon as diagnosis is established (8).…”
Section: Discussionmentioning
confidence: 99%